Perlindungan Hukum Badan Pengawas Obat Dan Makanan (BPOM) Terhadap Peredaran Produk Jamu Yang Mengandung Bahan Kimia Obat Berbahaya - Ni Kadek Ayu Padmi Ari Sudewi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Jurnal Analogi Hukum, 2020)
Traditional medicine in Indonesia or Jamu has been known for a long time. If in traditional medicine contains medicinal chemicals it is where there is an indication of violation of the rules of manufacture or composition of traditional medicines produced. This situation creates unrest among the people as consumers, because its rights have been violated. Weak consumer positions are weakening. Based on the background of the problem described above. Then can be formulated some of the following problems (1) How is the role of BPOM in the supervision of traditional herbal medicine that contains hazardous chemicals in the community? 2 How is legal protection against the public against the traditional herbal medicine that contains harmful chemicals under Law No. 8 of 1999 about consumer protection? Referring to the formulation of the problem, then the type of research used in the writing is normative research. Surveillance conducted by BPOM on the distribution of traditional herbal medicine is done both in production activities where the product has not circulated or supervision of products that have been circulating the market. The legal purpose of repressive legal protection is to resolve disputes. BPOM's preventive law efforts in the supervision of traditional herbs can be coaching and quality improvement policy by enforcing the standardization of production quality.